In Silico and In Vitro Studies of the Antimetastatic and Antiangiogenic Activities of Cordyceps militaris Extracts on Breast Cancer Cells (MDA-MB-231) - Chang, Alyssa Pei Qi; Khor, Sabrina Xin Yi; Chia, Adeline Yoke Yin; Chamyuang, Sunita; Tang, Yin-Quan (Journal of Medical Science, 2025)
Introduction. Cordyceps militaris (CM), a traditional medicinal fungus in East Asia, has garnered increasing attention due to its potential anticancer properties. Despite extensive use in traditional medicine, the mechanisms underlying its antimetastatic and antiangiogenic effects in breast cancer remain unclear. This study aimed to explore the bioactive components of aqueous extracts derived from CM’s mycelium (Aq-CMM) and fruiting body (Aq-CMF), focusing on their potential inhibitory activities on metastasis and angiogenesis in triple-negative breast cancer cells (MDA-MB-231).Materials and methods. In silico molecular docking was conducted to screen for key CM bioactive compounds and evaluate their binding affinities toward metastasis- and angiogenesis-related targets, NF-κB and VEGFR. In vitro cytotoxicity was assessed using 2D monolayer and 3D spheroid MDA-MB-231 cultures treated with Aq-CMM and Aq-CMF. Cell viability (IC50) was determined at 48 hours, and microscopic evaluation of treated spheroids was performed to assess morphological disruption.Results and conclusions. Docking analyses identified ergothioneine as a primary CM-derived compound with strong binding affinity to NF-κB (−7.83 kcal/mol) and VEGFR (−7.62 kcal/mol), suggesting potent inhibitory effects on metastatic and angiogenic pathways. In vitro assays showed that Aq-CMF exerted greater growth-inhibitory effects (IC50 = 54 µg/mL in 2D; 46 µg/mL in 3D) than Aq-CMM at 48 hours. Microscopic observations confirmed notable disruption of spheroid architecture following treatment. These findings highlight the therapeutic potential of ergothioneine-rich CM extracts, particularly from the fruiting body, as promising anticancer agents that warrant further mechanistic and translational studies.
Keywords: metastasis; angiogenesis; Cordyceps militaris; breast cancer